2005
DOI: 10.1021/jm058167w
|View full text |Cite
|
Sign up to set email alerts
|

Design and Studies of Novel 5-Substituted Alkynylpyrimidine Nucleosides as Potent Inhibitors of Mycobacteria

Abstract: We herein report a new category of 5-substituted pyrimidine nucleosides as potent inhibitors of mycobacteria. A series of 5-alkynyl derivatives of 2'-deoxyuridine (1-8), 2'-deoxycytidine (9-14), uridine (15-17), and 2'-O-methyluridine (18, 19) were synthesized and evaluated for their antimycobacterial activity in vitro. 5-Decynyl, 5-dodecynyl, and 5-tetradecynyl derivatives showed the highest antimycobacterial potency against M. bovis and M. avium, with the 2'-deoxyribose derivatives being more effective than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 24 publications
(68 reference statements)
4
75
0
Order By: Relevance
“…1, 1–10 ). 5–(1–Dodecynyl)– and 5–(1–tetradecynyl)–2ʹ–deoxyuridine ( 1 and 2 , respectively) used as a control were prepared by the method in [11]. 5–Alkyloxymethyl–pyrimidine nucleoside derivatives ( 6–10 ) were synthesized using our method in [15], and nucleoside 5ʹ–monophosphates ( 3–5 ) were synthesized by the method in [15–16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, 1–10 ). 5–(1–Dodecynyl)– and 5–(1–tetradecynyl)–2ʹ–deoxyuridine ( 1 and 2 , respectively) used as a control were prepared by the method in [11]. 5–Alkyloxymethyl–pyrimidine nucleoside derivatives ( 6–10 ) were synthesized using our method in [15], and nucleoside 5ʹ–monophosphates ( 3–5 ) were synthesized by the method in [15–16].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, 5–modified pyrimidine nucleosides with lengthy 1–alkinyl radicals have demonstrated an inhibitory effect on Mycobacterium tuberculosis and M. bovis in vitro [1114]. The best antibacterial activity has been demonstrated for nucleoside 5–(1–dodecynyl) and 5–(1–tetradecynyl) derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5-Dodecynyl (57, 60), 5-tetradecynyl (58) and 5-decynyl (59) derivatives of 2′-deoxyuridine and/or 2′-deoxycytidine showed moderate activity against M. bovis growth, with MIC 90 values ranging from 10 to 50 μg/ml ( Figure 13B), while the introduction of either a ribose sugar moiety or smaller 5-alkynyl chains induced a decrease in antitubercular activity [120].…”
Section: Nucleoside Analogs With Unclear Targetmentioning
confidence: 99%
“…In our subsequent studies, we designed, synthesized and examined a variety of 2-, 4-, 5-and/or 6-substituted/unsubstituted pyrimidine nucleosides containing various deoxyribose, ribose, arabinose, dideoxyribose and acyclic moieties. During our continued search of novel anti-TB agents, we found that 5-alkynyl substituted pyrimidine nucleosides were very potent inhibitors of mycobacteria (Rai et al, 2005). We , reported that pyrimidine nucleoside analogs 1--D-2'-arabinofuranosyl-5-dodecynyluracil (10), 1-(2'-deoxy-2'-fluoro--D-ribofuranosyl)-5-dodecynyluracil (11), and 1-(2'-deoxy-2'-fluoro--D-ribofuranosyl)-5-tetradecynyluracil (12) In the same year, we (Rai et al, 2007) further reported syntheses and evaluation of a series of 5-acetylenic derivatives of 2',3-dideoxyuridine, and 3'-fluoro-2',3'-dideoxyuridine for their antimycobacterial activity against M. bovis, Mtb, and M. avium.…”
Section: Cpzen-45mentioning
confidence: 99%